Movements of adaptation of the activities of the Education through Work for Health Program in the context of the covid-19 pandemic (Research, Society and Development, 2021)
The Education through Work for Health Program (PET-Saúde) aims to reorient professional training in health based on the inclusion of students in health services. The activities of the tutorial groups needed to be rethought due to the interruption of classroom activities because the covid-19 pandemic. This case study aimed to learn about the adaptation process of the tutorial groups for the development of activities in the context of the covid-19 pandemic. 32 members of PET-Saúde projects in the state of Rio de Janeiro were interviewed. Six adaptation movements were identified: redesigning actions, adapting to the use of digital technologies, intensifying intra-group activities, setting up support groups, supporting health departments, and health education through social media. Adaptation movements are flexible to adjustments, allowing groups to reflect and incorporate the complexity of the pandemic context and the needs of the community in the development of actions. The actions performed, planned, and structured collectively, respecting the limitations and vulnerabilities of students, preceptors, and tutors, demonstrate that it is possible to support the coping covid-19 pandemic, and to teach and learn from the everyday reality of health services, even if not in the front line.